The role of tau tubulin kinase 1 and 2 in TDP-43 pathology in ALS cellular model - Uski, Eveliina (My University, 2023)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that causes progressive degeneration of upper and lower motor neurons. Loss of motor neurons gives rise to voluntary muscle weakness and muscular atrophy, eventually leading to respiratory failure and death usually within 2-5 years after diagnosis. A common histopathological hallmark of ALS is the presence of cytosolic protein aggregates enriched with phosphorylated transactive response DNA-binding protein-43 (TDP-43). This protein, TDP-43, plays a crucial role in RNA metabolism, and its phosphorylation is suggested to contribute to the disease pathology of ALS by promoting TDP-43 aggregation and mislocalization from the nucleus to the cytoplasm. Recent studies have demonstrated that TDP-43 can be phosphorylated directly by Tau tubulin kinase 1 and 2 (TTBK1/2). In addition, TTBK1/2 expression is increased in the post-mortem motor cortex of ALS patients. This project aims to develop an in vitro TDP-43 phosphorylation/aggregation model and to study the role of TTBK1/2 in TDP-43 pathology. TDP-43 phosphorylation and aggregation were induced using TDP-43 overexpression and chemical stressors. The role of TTBK1/2 was studied using TTBK1/2 overexpression and inhibition (siRNA knockdown, small molecule inhibitors). Protein levels of TTBK1/2 were analyzed by western blot and immunofluorescence staining, and mRNA levels of TTBK1/2 were investigated by RT- qPCR. TDP-43 phosphorylation/aggregation was evaluated by western blotting of RIPA buffer fractions, representing soluble proteins, and urea buffer fractions, representing insoluble proteins. In the set-up of the TDP-43 phosphorylation/aggregation model, enrichment and phosphorylation of TDP-43 in urea fraction were observed after TDP-43 overexpression in HEK293 cells and mouse primary cortical cultures. In primary cortical cultures, stressor treatments induced TDP-43 phosphorylation at highly toxic concentrations. Western blot and/or immunofluorescence studies demonstrated successful TDP-43 and TTBK1/2 overexpression in both cell models. TTBK1/2 overexpression did not influence the phosphorylation of endogenous TDP-43. However, TTBK1/2 co-overexpression with TDP-43 led to robust TDP-43 phosphorylation and enrichment in urea fractions in HEK293 cells. Two TTBK1 inhibitors induced a relatively slight reduction of TDP-43 phosphorylation in HEK293 cells overexpressing TTBK1 and TDP-43. In mouse primary cortical cultures, efficient TTBK1/2 knockdown was achieved using siRNAs, but due to the time limit, the effect of TTBK1/2 knockdown on TDP-43 phosphorylation was not studied. The data in this project indicate that TTBK1/2 has a role in TDP-43 phosphorylation and aggregation. Further investigation is needed on whether TTBK1/2 inhibition could be a promising therapeutic approach for TDP-43 pathologies. Research in this area is essential since there is a critical unmet medical need for disease-modifying therapies for ALS.
Keywords: Amyotrophic lateral sclerosis, TDP-43, TDP-43 phosphorylation, Tau tubulin kinase 1, Tau tubulin kinase 2